Inhibitory Effect of β-Sitosterol on the Ang II-Induced Proliferation of A7r5 Aortic Smooth Muscle Cells - Yuankun Chen; Shumiao He; Ao Zeng; Siqing He; Xiaobao Jin; Chunmei Li; Wenjie Mei; Qun Lu (Analytical Cellular Pathology)
Context. Excessive proliferation of vascular smooth muscle cells (VSMCs) plays a critical role in the development of cardiovascular diseases. β-Sitosterol exerts protective effects against the cardiovascular disease. However, whether β-sitosterol protects against the excessive proliferation of VSMCs remain unclear. Objective. To explore the effects of β-sitosterol on VSMC proliferation. Materials and Methods. A7r5 cells were pretreated with 2 µM angiotensin II (Ang II) for 24 hr to establish an excessive VSMC proliferation model, followed by treatment with β-sitosterol for 24 hr. Cells were divided into five groups: control, Ang II, and Ang II + β-sitosterol (2, 4, 8 µM). CCK-8 assay, flow cytometry, and Ad-mCherry-GFP-LC3B assay analyzed cell proliferation, cell cycle, cell apoptosis, and autophagic flux. Additionally, the expression of proteins was detected by the western blotting. Results. β-Sitosterol effectively inhibited Ang II-induced A7r5 cell proliferation (IC50 : 6.841 µM at 24 hr). It achieved this by arresting cell cycle progression, promoting apoptosis, inhibiting autophagy, and suppressing the contractile–synthetic phenotypic switch. Mechanistically, β-sitosterol downregulated PCNA, Cyclin D1, and Bcl-2, while upregulating pro-caspase 3, cleaved-caspase 3, and Bax to induce cell cycle arrest and apoptosis. Additionally, it suppressed the contractile–synthetic phenotypic transformation by downregulating OPN and upregulating α-SMA. The Ad-mCherry-GFP-LC3B Assay and western blotting revealed β-sitosterol’s autophagy inhibitory effects by downregulating LC3, ULK1, and Beclin-1 while upregulating P62 expression. Discussion and Conclusion. This study found for the first time that β-sitosterol could inhibit the proliferation of A7r5 cells induced by Ang II. β-Sitosterol treatment may be recommended as a therapeutic strategy to prevent the cardiovascular diseases.